2022
DOI: 10.1101/2022.01.09.475572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimenter sex modulates mouse biobehavioural and pharmacological responses

Abstract: Differential rodent responses to the sex of human experimenters could have far reaching consequences in preclinical studies. Here, we show that the sex of human experimenters affects mouse behaviours and responses to the rapid-acting antidepressant ketamine and its bioactive metabolite (2R,6R)-hydroxynorketamine. We found that mice manifest aversion to human male odours, preference to female odours, and increased susceptibility to stress when handled by male experimenters. This male induced aversion and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It will also be necessary to report the age of the animal, given that sex differences change over time-becoming more apparent with puberty and showing differences in older age. It has also been found that, in some experiments, the sex of the researcher can influence the results of the study (317,318), so this should also be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be necessary to report the age of the animal, given that sex differences change over time-becoming more apparent with puberty and showing differences in older age. It has also been found that, in some experiments, the sex of the researcher can influence the results of the study (317,318), so this should also be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…One illustration of this is a recent discovery that the sex of the experimenter alters the metabolic pathway of ketamine in isogenic mice. This was ultimately traced back to the scent of human males compared the scent of human females 57 . Additionally, there are many other sources of within-subject environmental variation impacting cell states, such as time since feeding, circadian rhythm patterns, and so on – none of which can be completely controlled.…”
Section: Supplemental Notesmentioning
confidence: 99%
“…It may even be that the sex of the experimenter can affect outcomes. Whilst this has not been systematically investigated in EAE, as far as we are aware, there are several reports that rodents of both sexes are more stressed when the person doing the experiments on them is male, and that this can lead to differences in behavioral assays of pain and stress (142,143). This could potentially add another layer of complexity to investigation of the effects of biological sex on the pathophysiology of EAE.…”
Section: Effects On Other Cells and Systems And On Responses To Therapymentioning
confidence: 99%